PEMAHAMAN MASYARAKAT DUSUN BATU JARAN TENTANG PERCERAIAN - Adiyanto Adiyanto (Al-Amien Prenduan for Islamic Institute, 2021)
This study aims to find out how people's views about divorce in Pragaan Daya Village, Batu Jaran Hamlet. and To find out how the community and related institutions respond to divorce in Pragaan Daya Village, Batu Jaran Village. This research is a field research with a qualitative descriptive method. The method used to obtain data and information in this study the author uses several data collection techniques, namely observation, interviews, and documentation. Subjects in this study included village heads, kiai, village officials and the community. For the validity of the data, researchers used triangulation by matching the results of interview data with data obtained from the results of documentation, observation, and other finding data. From the research that has been done, it is found that; The community's view of divorce in Pragaan Daya village, Batu Jaran hamlet is a state of breaking the husband and wife bond due to certain things, causing the marital relationship to break up. And the number of divorce phenomena that occur in Pragaan Daya Village, Dusun Batu Jaran is interpreted by an event that is usually responded to by the surrounding community, in the sense that the community does not want many divorces to occur in their community, because certain factors will lead to mudorotan, the final solution is divorce. taken.